2017
DOI: 10.1590/1677-5449.005216
|View full text |Cite
|
Sign up to set email alerts
|

Associação entre sintomas, veias varicosas e refluxo na veia safena magna ao eco-Doppler

Abstract: Background: Chronic venous disease demands clinical assessment, quantification of hemodynamic effects, and definition of anatomic distribution before diagnostic and treatment decisions can be made. Methods: This is a prospective study conducted in 2015 with a sample of 1,384 patients (2,669 limbs) aged from 17 to 85 years, 1,227 of whom were female. The most common symptoms reported in response to the questionnaire were pain, tiredness, feelings of heaviness, burning, cramps, and tingling. Subsets were formed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
3
0
1
Order By: Relevance
“…18 In line with some other studies,18,19 we found altered reflux in the saphenofemoral junction in 81.8% of the limbs analyzed with GSV reflux in the thigh. Seidel et al 10 studied the association between CVI symptoms, visible varicose veins, and GSV reflux, grouping patients in three different groups (asymptomatic with varicose veins, symptomatic with no varicose veins, and symptomatic with varicose veins) and concluded that GSV reflux was more frequent in symptomatic patients with visible varicose veins, however they did not study the relevance of SFJ insufficiency on symptoms and on the level of varicose veins visible during the physical examination. Even though the presence of altered SFJ reflux is a relevant parameter for surgical recommendation 20 and predictor of CVI, 19 the presence of such reflux presented no correlation with the clinical classification of CVI (CEAP) in this study, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…18 In line with some other studies,18,19 we found altered reflux in the saphenofemoral junction in 81.8% of the limbs analyzed with GSV reflux in the thigh. Seidel et al 10 studied the association between CVI symptoms, visible varicose veins, and GSV reflux, grouping patients in three different groups (asymptomatic with varicose veins, symptomatic with no varicose veins, and symptomatic with varicose veins) and concluded that GSV reflux was more frequent in symptomatic patients with visible varicose veins, however they did not study the relevance of SFJ insufficiency on symptoms and on the level of varicose veins visible during the physical examination. Even though the presence of altered SFJ reflux is a relevant parameter for surgical recommendation 20 and predictor of CVI, 19 the presence of such reflux presented no correlation with the clinical classification of CVI (CEAP) in this study, i.e.…”
Section: Discussionmentioning
confidence: 99%
“… 2 , 3 Clinical assessment to assess anatomic distribution and to quantify the hemodynamic effects is needed to define the severity of the disease, because of its impact in terms of reduced quality of life and the chronic and subjective nature of complaints and symptoms such as pain, feelings of heaviness, swelling, cramps, and others. 1 , 6 , 7…”
Section: Introductionmentioning
confidence: 99%
“…Essa alta prevalência está associada a envelhecimento, obesidade, história familiar, sexo feminino (5:1), mulheres caucasianas, uso de anticoncepcional oral, terapia de reposição hormonal e atividades laborais em ortostatismo 2 , 3 . O impacto na redução da qualidade de vida aliado a cronicidade e subjetividade de queixas e sintomas como dor, sensação de peso, inchaço, câimbras, entre outros necessita de avaliação clínica para estabelecer a sua distribuição anatômica e quantificar os efeitos hemodinâmicos para definir a gravidade da doença 1 , 6 , 7 .…”
Section: Introductionunclassified
“…Once the disease establishes, it can progress to wounds of difficult healing, incapacities, and still recur in up to 66% by making the condition chronic (3) . Feeling of weight, pain and itching in the lower limbs (LL) (4) are often diagnosed clinical symptoms, and may be supplemented with Doppler-like imaging tests.…”
Section: Introductionmentioning
confidence: 99%